Oral Health in Brazil - Part I: public oral health policies - Junqueira, Simone Rennó; Pannuti, Cláudio Mendes; Rode, Sigmar De Mello [UNESP] (Sociedade Brasileira de Pesquisa Odontológica - SBPqO, 2008)
This paper reviews the historical development of public health policies in Brazil and the insertion of oral health in this context. Since 1988, Brazil established a Unified National Health System (Sistema Único de Saúde - SUS), which was conceived to assure access to health actions and services, including oral health. However, a history of lack of access to health services and the health problems faced by the Brazilian population make the process of building and consolidating the SUS extremely challenging. Since 2004, the Oral Health National Policy has proposed a reorientation of the health care model, supported by an adaptation of the working system of Oral Health teams so that they include actions of health promotion, protection and recovery. Human resources should be prepared to act in this system. The qualifying process must take in consideration knowledge evolution, changes in the work process and changes in demographical and epidemiological aspects, according to a perspective of maintaining a balance between technique and social relevance.
Keywords: Public health; Health policy; Oral health; Brazil